Christian ethos secondary schools in England and Wales a common voice or wide diversity? - Francis, Leslie J. 1947-; Casson, Ann; McKenna, Ursula (2018)
This study argues that it is the collective worldview of the students which is crucial in reflecting and shaping the ethos of schools. In order to understand the potential distinctiveness of Christian ethos schools two analyses were undertaken. The collective worldview of 2942 students attending 10 Christian ethos schools was compared with the collective worldview of 13,861 students attending 71 schools without a religious character. Then the collective worldview of 194 students attending an Anglican school that prioritised the Church's 'domestic' function in education was compared with the collective worldview of 302 students attending an Anglican school that prioritised the Church's 'general' function in education. The major difference occurs not between Christian ethos schools and schools without a religious character, but between Anglican schools that voice their interpretation of the Church's mission in education differently.
Keywords: Christian ethos; Church schools; quantitative research; student values